ANALISIS PEMECAHAN MASALAH MATEMATIS DITINJAU DARI GAYA BELAJAR SISWA PADA SPLDV - Nurul Mutmainnah Satriana; Firdaus, Andi Mulawakkan; Rezki Ramdani (Jurnal Penalaran dan Riset Matematika, 2025)
This study aims to determine the effect of using Block dienes media on mathematics learning outcomes in grade I students of UPT SPF SD Inpres Pa'Baeng-Baeng 1 and to analyze learning outcomes based on students' learning styles. The method used is a quasi-experimental design with a sample of 50 students, consisting of an experimental class (n = 25) and a control class (n = 25), which were taken through a saturated sampling technique. The instruments used were essay tests and observation sheets, with data analysis through descriptive statistics, normality tests, homogeneity, hypothesis tests, and N-Gain tests. The results showed that the experimental class obtained a significant increase in learning outcomes, with a distribution of 52% in the high category and 36% very high, and an average N-Gain of 0.77 (high category). Based on learning styles, students with a visual learning style showed the highest average score increase compared to auditory and kinesthetic. As many as 86.67% of students showed activeness in learning, and 87% gave a positive response to the use of media. Hypothesis testing shows that H₀ is rejected and H₁ is accepted, which means that there is a significant influence of the use of Block dienes media on students' mathematics learning outcomes, especially for students with a visual learning style